Mobilität organisieren. Rahmenbedingungen für ein effektives Mobilitätsmanagement. - Müller, Guido (Deutscher Verkehrs-Verl., 2004)
Mobilitätsmanagement ist ein effizienter verkehrspolitischer Ansatz, der flexibel einsetzbar ist und auf der Kooperation von Öffentlichen und Privaten basiert. Das EU-Projekt MOST (2000-2002) unter Koordination der Forschungsgesellschaft Mobilität (FGM-AMOR, Österreich; http://mo.st) hat die Rahmenbedingungen für eine breite Anwendung organisatorischer Lösungen im Verkehr untersucht. Aus der europäischen Analyse werden Empfehlungen für eine notwendige Agenda in Deutschland abgeleitet, um die Umsetzung von Mobilitätsmanagement zu fördern. difu

Mobility management is an efficient transport policy approach, that can be applied in a flexible way. Co-operation of public and private partners is one of its main characteristics. Examples from Europe show hat car trips to specific sites such as companies or schools can be reduced by 5-20 per cent depending on local conditions. Beside testing mobility management in 30 demonstration sites, the EU-funded research project MOST (http:/ /mo.st) has analysed the framework conditions for mobility management across Europe. In the last years there has been increasing activity in many countries, e.g. the Netherlands, Great Britain or Italy. The analysis has led to the) P.A.I.R.-scheme which structures the recommendations. From this scheme and the European best practise a 10-step action programme is proposed for Germany with a necessary agenda to advance the application of mobility management. difu
Keywords: Verkehr; Verkehrsinfrastruktur; Verkehrswissenschaft; Siedlungsentwicklung; Stadtverkehr; Ablauf; Verkehrssystem; Verkehrskonzept; Mobilität; Handlungsprogramm; Integrierte Verkehrsplanung; Mobilitätsmanagement; Verkehrsmanagement; EU-Projekt